Software Exorcism: A Handbook for Debugging and Optimizing Legacy Code - Blunden, Bill.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
YOU HAVE TO OWN THIS BOOK! Software Exorcism: A Handbook for Debugging and Optimizing Legacy Code takes an unflinching, no bulls$&# look at behavioral problems in the software engineering industry, shedding much-needed light on the social forces that make it difficult for programmers to do their job. Do you have a co-worker who perpetually writes bad code that you are forced to clean up? This is your book. While there are plenty of books on the market that cover debugging and short-term workarounds for bad code, Reverend Bill Blunden takes a revolutionary step beyond them by bringing our attention to the underlying illnesses that plague the software industry as a whole. Further, Software Exorcism discusses tools and techniques for effective and aggressive debugging, gives optimization strategies that appeal to all levels of programmers, and presents in-depth treatments of technical issues with honest assessments that are not biased toward proprietary solutions.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems